What’s in a Name? On Language, Concept Formation, and the Definition Disputes in the Entrepreneurship Literature - Jonsson Petur O. (Cultural Science)
When it comes to entrepreneurship, the conceptual framework of economics is disjointed: On the one hand almost everyone agrees that entrepreneurial initiative and creativity are critical for economic progress. On the other hand neither initiative, nor creativity, plays any role in formal models of choice and economic behavior. This creates a blind spot on the behavioral aspects of entrepreneurship. It has also spawned a dichotomy between the functional and behavioral aspects of entrepreneurial actions in the economics literature. Most importantly, it prevents economists from developing a coherent unifying theoretical framework for making sense of entrepreneurs. The problem is reinforced by the language and semiotics of economics and is reflected by the lack of behavioral research on entrepreneurs in the literature. As suggested by Baumol (1968 and 2010) initiative and creativity are the obvious defining traits of entrepreneurship. Even so, the literature has spawned a variety of different and occasionally nonsensical definitions of entrepreneurship that obscure and divert our attention away from these defining characteristics. The divergent definitions in the literature are further exacerbated by discordant conceptual structures and ideas that cannot easily be translated from one field to another. In the absence of a unifying framework, different fields have focused narrowly on entrepreneurship from dissimilar angles. The bottom line is that researchers in different fields sometimes rely on such incompatible definitions of what constitutes entrepreneurship that interdisciplinary dialogue is impossible. The end result is akin to the problem of radical translation between different languages. The paper concludes that the definition debates will not be resolved without a unifying structure that focuses on initiative and creativity as the defining attributes of entrepreneurship. This calls for some new tools and behavioral models that can explicitly account for initiative and creativity as integral aspects of human choices and actions.